2017
DOI: 10.1016/j.atherosclerosis.2017.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Soluble TWEAK and atheromatosis progression in patients with chronic kidney disease

Abstract: Lower sTWEAK concentrations are associated with atherosclerotic burden and atheromatosis progression in CKD patients free of clinical CVD. These data suggest that sTWEAK could serve as a biomarker to predict CV risk before clinical manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
1
15
0
2
Order By: Relevance
“…It has been demonstrated that sTWEAK levels are associated with the presence and progression of acute or chronic disease. 19,21,30,31 However, the plausible regulation of sTWEAK levels and Fn14 expression during anaphylaxis is still unknown. By using 2 experimental mouse models that simulate different degrees of allergic sensitivity, we have evaluated circulating sTWEAK concentrations in blood samples and TWEAK expression in lungs.…”
Section: Expression Of Tweak and The Fn14 Receptor Increase In Mouse mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that sTWEAK levels are associated with the presence and progression of acute or chronic disease. 19,21,30,31 However, the plausible regulation of sTWEAK levels and Fn14 expression during anaphylaxis is still unknown. By using 2 experimental mouse models that simulate different degrees of allergic sensitivity, we have evaluated circulating sTWEAK concentrations in blood samples and TWEAK expression in lungs.…”
Section: Expression Of Tweak and The Fn14 Receptor Increase In Mouse mentioning
confidence: 99%
“…15,16 TWEAK/Fn14 interaction plays a crucial role in a variety of pathologic inflammatory disorders, such as atherosclerosis, cardiac dysfunction, diabetes, and chronic kidney disease. [17][18][19][20] TWEAK/Fn14 has also been suggested as a potential target to limit edema formation, a major problem in patients with stroke. 21 In addition, it has been suggested that TWEAK/Fn14 signaling is relevant to angiogenesis.…”
mentioning
confidence: 99%
“…Out of those, 481 had available plasma samples to measure FGF-2 levels. Samples from the other patients had already been spent to measure other biomarkers in sub-studies within the NEFRONA study (22,23). In any case, both populations did not differ in most of the parameters of the study, although there was a lower proportion of patients in dialysis than in the total sample.…”
Section: Design and Study Populationmentioning
confidence: 99%
“…TWEAK is expressed in several tissues (i.e., heart, brain, and lung) and cells (endothelial and smooth muscle cells). Human studies showed that in patients with chronic kidney disease, sTWEAK was associated with impaired FMD [10,11] and atheromatosis progression [12]. It was also found that in artery samples from patients with atherosclerosis, sTWEAK concentrations were correlated with increased carotid intima-media thickness (c-IMT), a hallmark of subclinical atherosclerotic disease [13].…”
Section: Introductionmentioning
confidence: 99%